Developing Company Images Through Spiritual Public Relations Facing Covid-19 Outbreak - Kunaifi, Aang; Qomariyah, Lailatul (Jurnal Iqtisaduna, 2021)
Public Relations is the company's functional organ in building an image aimed at gaining public trust as a potential market. Through this trust the value of a company has increased, both in aspects of customer loyalty and corporate profits. The ability to increase the value of the company will be the strength to win the competition, so the company is able to maintain sustainability and experience growth. Based on that, a strategy to build and maintain an image is needed. So it is very interesting to examine how the strategy of building a corporate image in the situation of intense business competition and dynamic social change. Therefore, the author tries to conduct studies and research in the field of spiritual public relations. This research was conducted at the Cahaya Berlian Pamekasan Hotel in East Java, with a focus on how the implementation of the public relations strategy at the sharia hotel and what was done by the management in building and maintaining the company's image. The uniqueness as the only sharia hotel at Pamekasan requires management to display spiritual differentiation, this is where the points to be obtained by researchers. Besides other facts, the company's ability to survive in a pandemic condition is an interesting plus point to be investigated. To get comprehensive information, researchers interviewed informants directly from the owner, manager, employees, customers, and the community around the hotel. The results showed that the application of the public relations strategy was done through a human relations approach, and the media relations strategy was implemented according to their respective goals. Human relations approach, aimed at maintaining internal and external relations of the company environment. So that good relations between fellow employees, stake holders, customers, the community and regulators are harmoniously established. As for media relations, it is intended to build and maintain a general corporate image through social media and direct communications. In another aspect, this study also found the importance of the owner's spiritual character. This spiritual character has created public sympathy that is relevant to the general purpose of the company. The above proves that there are three things that must be considered in building the company's image through the spiritual strategy of public relations, namely the value of public relations itself, human relations and media relations, and the third is the personal character of the owner. So that the target of public relations activities to be effective for improving the company's image